Improved Signal Coding Techniques For Broadband Power Line Communications - Shafieipour, Mohammad (2010)
This dissertation studies digital signal processing techniques for communications over power lines. In spite of the availability of power line communication (PLC) equipment, this technology is far from utilizing the full potential of power line networks which are more pervasive than any other wired communication alternative and should not be neglected by the engineering community. In this work, we have endeavored to fill the gap between the existing PLC technology and the ideal one which in theory is capable for exploiting the full potential of the accessible power grid for communication purposes.